The Role of Kaizen concept on quality improvement in motor vehicle assembly plants in Kenya - Motirei, Charles Ondieki (Strathmore University, 2020)
Kaizen is a well-recognized concept and highly revered in the manufacturing cycles all over the world because it stands for continuous improvements at the workplace with the participation, support of all employees and commitment of top management. Quality sits at the highest level in most organizations that value customers and the experience that comes with their products and services. The manufacturing pillar is one of the BIG 4 agendas that form the strategic plans of the government in pursuit of economic growth. Interestingly, auto industry is one on the key players in the manufacturing sector. The research was carried out to establish the impact of 5S KAIZEN on quality improvement in the motor vehicle assembly plants. Kenya, being the only country in the region that assembles motor vehicles for domestic and export market, it was deemed important to understand how quality improvement is enhanced by practicing Kaizen, one of the most famous and basic Japanese industrial practices and methodology. The target population of this study was 230 from 3 motor vehicle assembly plants from which a sample size of 146 employees was drawn through both simple random and stratified sampling. These employees were drawn from the technicians in production shop floor including the supervisory team of production managers, quality control managers and the Kaizen champions who are in charge of technical operations in the assembly plants. From the study, the response rate was 93.2% representing 136 of the 146. The study employed multiple regression analysis to study the relationship between quality improvement in the motor vehicle plants and the 5S kaizen. The study findings indicated that set in order was the most impactful on the quality improvement of motor vehicle with a beta coefficient of 0.866 in which it accounts for 61.0% variability in quality improvement. From the multiple regression the study established that the 5S kaizen significantly contribute to the quality improvement in the motor vehicle plants. However, these may prove to be of challenge owing to lack of financial resources, lack of support by the top management, lack of motivation from the employees and lack of skilled manpower.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Quality management; Motor vehicle assembly; Kaizen